VOLALITAS HARGA DAGING SAPI DI JAWA TIMUR PADA BULAN RAMADHAN - Priyambodo, Ayu Wulandari; Rinanti, Rosyida Fajri; Trianawati, Anis; Aviolita P. P, Aviva (BUANA SAINS, 2023)
This study aimed to investigate how the price of beef in East Java is affected by Ramadan. This study used ARCH/GARCH model to determine the correlation. The impact of Ramadan on the price beef in East Java is then examined, along with the effect of price fluctuations and price volatility, using the GARCH model. The results showed that price volatility affects variations in beef prices. Then, the GARCH (1,1) model estimation findings demonstrate that the volatility from the prior period and yesterday's variation in East Java have impacted changes in beef prices.